Peran Serikat Pekerja dalam Membangun Hubungan Industrial yang Harmonis - Ulwan Taqi Laudza; Sayed Haikal Fuad; Mohamad Zein Saleh (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Workers are a vital element in the development of the business world and play a crucial role within companies. Industrial relations aim to create a harmonious and mutually beneficial relationship between employers, workers, and the government. Trade unions hold a significant role in preventing workplace conflicts through various functions and effective communication skills. This study aims to evaluate the strategic function of trade unions in fostering harmonious industrial relations in the workplace. Positive industrial relations are essential to achieving productivity, job stability, and employee well-being. The method used in this study is a descriptive qualitative approach. The findings reveal that trade unions act as a bridge between employees and management, serving as a channel for voicing aspirations and resolving disputes. The success of trade unions in fulfilling their role is strongly influenced by managerial openness, government regulatory support, and the internal capabilities of the union organization. These results reinforce that tripartite collaboration among employers, labor, and the government is essential for creating a healthy and sustainable work environment.